Maturation of Auditory Cortex Neural Activity in Children and Implications for Auditory Clinical Markers in Diagnosis - Edgar, J. Christopher; Blaskey, Lisa; Green, Heather L.; Konka, Kimberly; Shen, Guannan; Dipiero, Marissa A.; Berman, Jeffrey I.; Bloy, Luke; Liu, Song; McBride, Emma; Ku, Matt; Kuschner, Emily S.; et al. (Frontiers in Psychiatry, 2020)
Functional brain markers that can inform research on brain abnormalities, and especially those ready to facilitate clinical work on such abnormalities, will need to show not only considerable sensitivity and specificity but enough consistency with respect to developmental course that their validity in individual cases can be trusted. A challenge to establishing such markers may be individual differences in developmental course. The present study examined auditory cortex activity in children at an age when developmental changes to the auditory cortex 50 ms (M50) and 100 ms (M100) components are prominent to better understand the use of auditory markers in pediatric clinical research. MEG auditory encoding measures (pure tone stimuli) were obtained from 15 typically developing children 6 to 8 years old, with measures repeated 18 months and 36 months after the initial exam. MEG analyses were conducted in source space (i.e., brain location), with M50 and M100 sources identified in left and right primary/secondary auditory cortex (Heschl’s gyrus). A left and right M50 response was observed at all times (Time 1, Time 2, Time 3), with M50 latency at Time 3 (76 ms) 10 ms earlier than Time 1 (87 ms; p < 0.001) and with M50 responses on average (collapsing across time) 5 ms earlier in the right than left hemisphere (p <0.05). In the majority of children, however, M50 latency changes were non-linear across the three-year period; for example, whereas in some children a 10 ms latency reduction was observed from Time 1 to Time 2, in other children a 10 ms latency reduction was observed from Time 2 to Time 3. M100 responses, as defined by a significant “peak” of detected power with opposite magnetic field topography and occurring 50-100ms later than the M50, were not observed in the majority of children at any time point. In sum, longitudinal findings showed large between- and within-subject variability in rate of change as well as time to reach neural developmental milestones (e.g., presence of a detectable M100 response). Findings also demonstrated the need to examine whole-brain activity, given hemisphere differences in the rate of auditory cortex maturation.